Reproductive disorders in Corriedale ewes - ISLAM, RAFIQUL; NADROO, G A; SARKAR, T K; BHAT, A S (The Indian Journal of Animal Reproduction, 2023)
Reproductive disorders ofCorriedale ewes were studied for twelve years (1992-2003) at Sheep research station,SKUAST-K, Srinagar. The reproductive disorders recorded were dry ewes, abortion, stillbirths, dystocia, lamb died due todystocia, ewes died before lambing and retained placenta. The occurrence of reproductive disorders varied significantly among the years. Out of total reproductive disorders, dry ewe percentage was highest (2.19 to 80.86 %; Av. 23.62 %) and retained placenta was lowest (0.03%). Incidence of other disorders recorded were abortion 0.25 %, still births 1.60 %, dystocia 1.23 %, lamb dieddue to dystocia 0.43% and ewes died before lambing 6.87 %. The incidence of lamb mortality within 24 hours (0 to 2.86 %; Av. 1.04 %), lambs died due to poor mothering ability (0 to 4.5 %; Av. 1.31 %) and mastitis (0 to 1.90 %; Av. 0.71 %) varied significantly among the years.
Keywords: Corriedale sheep; reproductive disorders; postnatal mortality; yearly variation